KONSEP AL-SARFAH DALAM KEMUKJIZATAN AL-QUR’AN - Abdurrahman Abdurrahman (IAIN Manado, 2021)
Abstract: The Quran is one of the miracles of the Prophet Muhammad that will never be matched until the Day of Resurrection, but it is different from the understanding of the followers of al-Sarfah who claim that humans can match and create something like the Quran but that ability is removed by Allah Swt. this is what they call al-s̩arfah understanding. This understanding is expressed descriptively and qualitatively, namely by analyzing and revealing data according to the research theme. Then the understanding of al-s̩arfah is found, namely the belief that Allah turns away the ability or desire of people who can make things like the Quran, or their enthusiasm is the removed to make things like Quran. Later, it was found that this understanding would be easier when it was related to the theological principles used by the Mu’tazilites as one of the originators of this understanding, namely the basis of Mu’tazilah understanding with the concept of free will and free act or qadariyah. Furthemore, opinions are expressed in the from of rebuttals from the theologians regarding this understanding and their arguments, and at the end, the implication of thr existence of this understanding of al-s̩arfah are revealed.Key Words: the Quran, miracle, al-s̩arfah Abstrak: Al-Qur’an merupakan salah satu mukjizat nabi Muhammad saw. yang tidak akan pernah dapat ditandingi sampai hari kiamat, namun berbeda dengan pemahaman pengikut al-s̩arfah yang mengklaim bahwa manusia mampu menandingi dan membuat yang semisal dengan Al-Qur’an namun kemampuannya itu dihilangkan oleh Allah Swt., inilah yang mereka sebut dengan paham al-s̩arfah, paham ini diungkap secara deskriptif kualitatif yaitu menganalisa dan mengungkap data sesuai dengan tema penelitian, kemudian didapati pengertian paham al-s̩arfah yaitu keyakinan bahwa Allah memalingkan kemampuan atau keinginan orang yang dapat membuat semisal dengan Al-Qur’an, atau semangat mereka dihilangkan untuk membuat yang semisal dengannya, selanjutnya didapati paham ini sesungguhnya akan semakin mudah dimengerti ketika dihubungkan dengan asas teologi yang dipakai oleh penganut mu’tazilah sebagai salah satu pencetus paham ini, yaitu basis paham mu’tazilah dengan konsep free will dan free act atau qadariyahnya, selanjutnya diungkap pendapat yang berupa bantahan para ulama tentang paham ini beserta dalilnya dan di akhir diungkap implikasi dari adanya paham al-s̩arfah ini. Kata kunci: Al-Qur’an, mukjizat, al-s̩arfah